Global Education in Canadian Elementary Schools: An Exploratory Study - Mundy, Karen; Manion, Caroline (Canadian Journal of Education/Revue canadienne de l'éducation, 2008)
This article reports on the implementation of global education in Canadian element- ary schools. Curriculum analysis and 76 interviews at school, ministry, and district levels revealed limited coordination among ministry, district and NGO efforts and little support for curriculum development and teacher training. In schools, fund- raising for international charities is often equated with global education, while other aspects of global learning are neglected. Equating global education with fundraising raises concerns for less affluent communities. We argue that more comprehensive and systematic government support for global education, and greater collaboration among ministries, NGOs, and schools is needed for Canadian children to receive an equitable, quality introduction to global citizenship. Key words: global citizenship, non-government organizations, social studies, teacher support Cet article fait le point sur l’implantation de l’éducation planétaire dans les écoles primaires au Canada. L’analyse des programmes scolaires et 76 entrevues menées dans des écoles, dans les ministères et dans des arrondissements scolaires ont révélé qu’il existait une coordination restreinte entre le ministère, les arrondissements scolai- res et les efforts des ONG et peu de soutien pour l’élaboration de programmes scol- aires et la formation des enseignants. Dans les écoles, la collecte de fonds pour des organismes de bienfaisance internationaux est souvent assimilée à l’éducation planét- aire tandis que d’autres aspects de l’éducation interculturelle sont négligés. L’assimilation de l’éducation planétaire aux collectes de fonds soulève des préoccupa- tions pour les collectivités moins fortunées. Les auteurs soutiennent qu’il faut un soutien gouvernemental plus exhaustif et systématique de l’éducation planétaire et une collaboration accrue entre les ministères, les ONG et les écoles pour que tous les enfants canadiens reçoivent une initiation de qualité à la citoyenneté mondiale. Mots clés : citoyenneté mondiale, organisations non gouvernementales, sciences hu- maines, soutien aux enseignants